Metode Pembelajaran Pendidikan Islam: (Telaah Hadis Tarbawi) - Hidayat, Rahmat; Mujiburrahman; Habiburrahim; Silahuddin (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
Learning methods are the methods or techniques for presenting lesson materials that will be used by teachers when presenting lesson materials, either individually or in groups. In order to achieve the learning objectives that have been formulated. Meanwhile, the aim of Islamic education is to increase understanding of Islamic teachings, skills in practicing them, and increase the practice of Islamic teachings in life. So, in summary, it can be said that the aim of Islamic education is religious, namely becoming a Muslim with serious religious intensity and based on strong faith, with the main aim being the formation of good morals. Because that is the origin of Islamic teachings, and it can be traced through the Qor’an and Hadith. So the author wants to look at several learning methods that he applies, by looking at several hadiths that can be used as the basis for learning methods.